Transcriptional Responses of Herbaspirillum seropedicae to Environmental Phosphate Concentration - Grillo Puertas, Mariana (2021)
Herbaspirillum seropedicae is a nitrogen-fixing endophytic bacterium associated with important cereal crops, which promotes plant growth, increasing their productivity. The understanding of the physiological responses of this bacterium to different concentrations of prevailing nutrients as phosphate (Pi) is scarce. In some bacteria, culture media Pi concentration modulates the levels of intracellular polyphosphate (polyP), modifying their cellular fitness. Here, global changes of H. seropedicae SmR1 were evaluated in response to environmental Pi concentrations, based on differential intracellular polyP levels. Cells grown in high-Pi medium (50 mM) maintained high polyP levels in stationary phase, while those grown in sufficient Pi medium (5 mM) degraded it. Through a RNA-seq approach, comparison of transcriptional profiles of H. seropedicae cultures revealed that 670 genes were differentially expressed between both Pi growth conditions, with 57% repressed and 43% induced in the high Pi condition. Molecular and physiological analyses revealed that aspects related to Pi metabolism, biosynthesis of flagella and chemotaxis, energy production, and polyhydroxybutyrate metabolism were induced in the high-Pi condition, while those involved in adhesion and stress response were repressed. The present study demonstrated that variations in environmental Pi concentration affect H. seropedicae traits related to survival and other important physiological characteristics. Since environmental conditions can influence the effectiveness of the plant growth-promoting bacteria, enhancement of bacterial robustness to withstand different stressful situations is an interesting challenge. The obtained data could serve not only to understand the bacterial behavior in respect to changes in rhizospheric Pi gradients but also as a base to design strategies to improve different bacterial features focusing on biotechnological and/or agricultural purposes.